Tail risk in commercial property insurance - Enrico Biffis; Erik Chavez (Risks, 2014)
We present some new evidence on the tail distribution of commercial property losses based on a recently constructed dataset on large commercial risks. The dataset is based on contributions from Lloyd's of London syndicates, and provides information on over three thousand claims occurred during the period 2000 - 2012, including detailed information on exposures. We use occupancy characteristics to compare the tail risk profiles of different commercial property exposures, and find evidence of substantial heterogeneity in tail behavior. The results demonstrate the benefits of aggregating granular information on both claims and exposures from different data sources, and provide warning against the use of reserving and capital modeling approaches that are not robust to heavy tails.
Keywords: 330; commercial property insurance; exposure rating; heavy tails; tail index; tail regression